Treatment cost on Visceral Leishmaniasis: Case study in endemic districts of Nepal - Baral, Dharanidhar (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Approximately six million people are at risk of infection from Visceral Leishmaniasis (VL) in Eastern and middle plain region of Nepal. The disease affects the rural poor socio-economical community causing significant death among untreated patients (Per capita income of Nepal US $ 400.00). An effort was made to estimate treatment cost on clinically diagnosed VL patients in three VL endemic districts of Eastern development region of Nepal. Materials & Methods: During one and half year period in 2012/2013, approximately 500 cases were diagnosed as VL from three district hospitals; two zonal hospitals and one tertiary level hospital of Eastern Terai districts of Nepal. Total 172 cases were selected randomly from the three VL endemic districts of Eastern Nepal and interviewed at their homes. Results: On an average, cost for VL treatment during hospitalization was Nepali Rupees (NRS) 4032.67±313.47, where median (IQR) length of hospital stay was 17 (five to 35) days. The patients were iagnosed symptomatically as VL after 45 ± 6 days of feeling illness. The treatment cost of patient before diagnosis was NRS 2379.93 ± 202.30. Patient reached the treatment center after 17 ± 2 days of diagnosis and referral from community level. Total 83.7% patients came for follow-up after average 30 ± 2 days of discharge with an average expense of RS 360.34 ± 49.88. The death rate of VL patients during treatment and within one month of discharge was 7.6%. It was found that the average funeral cost was NRs 9598.00 ± 1259.00. Conclusion: This study concludes that, average treatment cost for VL treatment during hospital stay was NRs 4032 and before treatment was around NRS 2380 and follow up cost was NRs 360. Early diagnosis and treatment in treatment center without significant delay can not only reduce the hospital stay and treatment cost, but also saves life of VL patients. JCMS Nepal. 2016;12(2):60-5